User Impersonation Project - Ergas, Jonathan (Wellington Faculty of Engineering Symposium, 2023)
Volpara Health is a company focused on finding ways to detect breast cancer with AI in the early stages before it becomes lethal. They have a customer facing application that helps clinicians better assess if their clients have a possibility of breast cancer. Currently, Volpara has no system in place that allows a support team member to log in as one of their clients to help diagnose issues/problems with the dashboard without the client needing to provide their login information. This causes a lot of issues with privacy and security as anyone with the login information of users can access confidential files and other internal systems. This led to the need for a custom solution that allows the impersonation of a user to access the dashboard and no other service. This project provides the desired custom solution that would allow the support staff to check the customers’ dashboard quickly and efficiently for their issues causing less downtime and a better customer support experience. Tools used for developing the project include TypeScript, Angular for the front-end and C#(.Net) for the backend. The performance and security of this project are key, this requires website and backend load tests and performance metrics, as well as security tests to make sure all sensitive methods require authorization to be executed and that the website cannot be bypassed in any way to gain sensitive information. On top of these tests are user tests to make sure the solution is easy and straightforward to use without the need for extra training that would cause more overhead for Volpara Health.